Programming cytomegalovirus as an HIV vaccine - Picker, Louis J.; Lifson, Jeffrey D.; Gale, Michael; Hansen, Scott G.; Früh, Klaus (Trends in immunology, 2023)
Non-human primate (NHP) cytomegaloviruses (CMVs) can be genetically modified to induce unconventional CD8+ T cell responses that target epitopes presented by MHC-II and MHC-E; the latter is an MHC-Ib molecule with limited polymorphism, primarily known for regulating natural killer (NK) cell reactivity. These unconventional responses to diverse antigens are inhibited by specific gene products in wild-type NHP CMVs, and are enabled by deletion of these genes.Based on understanding how CMV controls CD8+ T cell priming, Rhesus (Rh) CMV-based vaccine vectors can be programmed to elicit vaccine insert-specific CD8+ T cell responses that recognize peptide epitopes presented by MHC-Ia, MHC-II, and MHC-E, alone and in combination, generating the first vaccine with programmable CD8+ T cell epitope targeting.RhCMV-based vaccine vectors that elicit simian immunodeficiency virus (SIV)-specific, MHC-E-restricted CD8+ T cells, but not other conventional or unconventional MHC restriction CD8+ T cell response types, mediate a potent form of efficacy against highly pathogenic SIV; viral replication is completely arrested in early primary infection, and virus is cleared over ensuing months to several years.SIV replication arrest protection occurs in ~60% of vaccinees with MHC-E-restricted CD8+ T cell responses and correlates with a vaccine-induced innate immune response featuring IL-15 signaling.All known RhCMV gene product-mediated CD8+ T cell response programming functions are conserved in the human CMV genome, suggesting that HIV-1-specific MHC-E-restricted CD8+ T cells and their associated replication arrest and clear efficacy could be recapitulated in humans. HIV and SIV are highly immune evasive viruses with few immune vulnerabilities. The discovery that CMV vector-programmed MHC-E-restricted CD8+ T cells can mediate complete replication arrest of primary SIV infection with subsequent viral clearance indicates the existence of a previously unknown Achilles’ heel that offers promise for vaccines or immunotherapeutics for HIV, and possibly other infectious diseases or cancer. The initial development of cytomegalovirus (CMV) as a vaccine vector for HIV/simian immunodeficiency virus (SIV) was predicated on its potential to pre-position high-frequency, effector-differentiated, CD8+ T cells in tissues for immediate immune interception of nascent primary infection. This goal was achieved and also led to the unexpected discoveries that non-human primate (NHP) CMVs can be programmed to differentially elicit CD8+ T cell responses that recognize viral peptides via classical MHC-Ia, and/or MHC-II, and/or MHC-E, and that MHC-E-restricted CD8+ T cell responses can uniquely mediate stringent arrest and subsequent clearance of highly pathogenic SIV, an unprecedented type of vaccine-mediated protection. These discoveries delineate CMV vector-elicited MHC-E-restricted CD8+ T cells as a functionally distinct T cell response with the potential for superior efficacy against HIV-1, and possibly other infectious agents or cancers.